2013
DOI: 10.1016/j.jpha.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and wavelength choice on in-situ dissolution test of Cimetidine tablets

Abstract: The effects of temperature and wavelength choice on in-situ dissolution test instrument of Cimetidine were studied. Absorbance (A)<1.0 is required when using a fiber-optic dissolution test system. The detection wavelength of λmax (218 nm) was replaced by 244 nm to carry out this test. The absorbance of Cimetidine solution at different temperature showed an obvious change. Calibration of Cimetidine solution should be tested at the same temperature (37° C) with the test solution. A suitable wavelength with small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The relationship between SO2 concentration and UV absorbance may be affecte various atmospheric parameters, such as humidity, gas flow rate, and temperature [16 To study the influence of environmental factors, experiments have to be conducted w one varying variable while all other variables are kept under control. To achieve this g a special device was developed for this study, as shown in Figure 2.…”
Section: Control Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between SO2 concentration and UV absorbance may be affecte various atmospheric parameters, such as humidity, gas flow rate, and temperature [16 To study the influence of environmental factors, experiments have to be conducted w one varying variable while all other variables are kept under control. To achieve this g a special device was developed for this study, as shown in Figure 2.…”
Section: Control Set-upmentioning
confidence: 99%
“…The relationship between SO 2 concentration and UV absorbance may be affected by various atmospheric parameters, such as humidity, gas flow rate, and temperature [16,17].…”
Section: Control Set-upmentioning
confidence: 99%
“…Figure 8 shows the temperature dependence of the spectra, with a lower absorbance signal at room temperature than that at 450 °C. Higher temperatures increase the molecular vibration and rotation movements and therefore increase the absorbance [44]. In order to avoid temperature effects on the absorbance signal, all K-M and baseline scans were acquired at room temperature for analysis.…”
Section: Kubelka-munk Scans and Calibrationmentioning
confidence: 99%